Specyfika świętości bł. Edmunda Bojanowskiego - Kardynał Grocholewski, Zenon (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In the past mostly clergymen and members of the institutions of the consecrated life were canonized. However, the Second Vatican Council was trying to change this, emphasizing the common call to holiness. St. John Paul II, who beatified and canonized many laymen, pointed out that “there are many paths to holiness and they are designed to fit different calls”. The holiness of Bl. Edmund Bojanowski (1814-1871) was characterized by his spiritual healthy teaching of lay people (being in a sense the “precursor” of the above-mentioned Council) and also by following the path which life and circumstances made available for him rather than seeking a specific path to holiness. Moreover, while analyzing his life, it is easy to illustrate the fact that holiness does not ruin anything, but makes everything better.